2020
DOI: 10.1021/acsaem.0c02319
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated Poly(ether sulfone)-Coated and -Blended Nafion Membranes with Enhanced Conductivity and Reduced Hydrogen Permeability

Abstract: Nafion, as a perfluorosulfonic acid (PFSA)-based polymer, is a key material that contributes to the commercialization of proton exchange membrane fuel cells (PEMFCs). The high dependence on relative humidity (RH) of Nafion or other PFSA membranes for proton conduction, together with its decreased mechanical and dimensional stability and high fuel (H 2 ) crossover at the cell operating temperatures (80 °C or above), however, remain issues that have yet to be solved. In the current work, thin sulfonated poly(ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Also, the fuel cell performances of the semi-IPN composite membrane (NPP-95) and the re-Nafion membrane developed in this study were compared with those of the Nafion-based semi-IPN composite membranes used for PEMFC reported elsewhere (Figure S12). ,, ,,, It was found that the PEMFC performance of our semi-IPN membranes based on cross-linked PAA–PVA and Nafion was significantly higher than that of most other Nafion-based semi-IPN composite membranes. This result strongly indicates that our NPP-95 membrane has high practical PEMFC applications.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Also, the fuel cell performances of the semi-IPN composite membrane (NPP-95) and the re-Nafion membrane developed in this study were compared with those of the Nafion-based semi-IPN composite membranes used for PEMFC reported elsewhere (Figure S12). ,, ,,, It was found that the PEMFC performance of our semi-IPN membranes based on cross-linked PAA–PVA and Nafion was significantly higher than that of most other Nafion-based semi-IPN composite membranes. This result strongly indicates that our NPP-95 membrane has high practical PEMFC applications.…”
Section: Resultsmentioning
confidence: 87%
“…The amount of hydrogen permeated through membranes can be measured by counting the number of these ejected electrons. 46,53 The results showed that the hydrogen permeability of NPP-95 was significantly lower at 0.62 mA/cm 2 than that of re-Nafion at 1.46 mA/cm 2 . These results were consistent with the hydrogen permeability test results described earlier indicating that the semi-IPN membrane was highly effective at suppressing hydrogen crossover even under actual fuel cell operating conditions.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Relative to Nafion-112, the sPES-Nafion membrane exhibited a high proton conductivity, a low hydrogen permeability, and improved mechanical and dimensional stabilities. 19 Furthermore, the membranes with multilayered structure have been constructed through the alternate deposition of components by spin coating method. 20,21 In our previous study, the proton conductivity of PA doped membranes based on polyvinylidene fluoride (PVDF) reached 7.70 Â 10 À2 S/cm at 160 C. 21 However, there was a concern of performance degradation due to PA molecules leakage after a longterm operation in consideration of the lack of strong containers to anchor PA molecules.…”
Section: Introductionmentioning
confidence: 99%